Non-Formal Educational Interactions (Case Study of Ojek Kers) in Panorama, Guguak Length District, Bukittinggi City - Sintia sumarlin; Solfema Solfema (Universitas Negeri Padang, 2023)
This research is motivated by work as motorcycle taxi drivers when they are at the base where they rest while waiting for passengers, when they get together they interact, exchange stories and share experiences, obtain information when motorcycle taxi drivers interact and communicate with fellow motorcycle taxi drivers as well as with passengers, which results in changes behavior of the non-formal education interaction process This research uses a qualitative approach with a case study type which is expected to provide an overview of the research results. The setting of this research was carried out at the Panorama motorcycle taxi base in Bukittinggi. The source of this research was obtained from motorcycle taxi drivers. Data collection techniques used in this study were interviews, observation and documentation. The validity of the data obtained from this study is by triangulation of data sources. The results of the study show that: (1) There are non-formal educational interaction activities about social activities among motorcycle taxi drivers, (2) There are non-formal educational interaction activities about managing finances, (3) There are interactions reminding each other in maintaining health (4) There are interaction activities non-formal education among motorcycle taxi drivers in the religious field.